Characteristics of teams, staff and patients: associations with outcomes of patients in assertive outreach. - Priebe, S; Fakhoury, W; White, I; Watts, J; Bebbington, P; Billings, J; Burns, T; Johnson, S; Muijen, M; Ryrie, I; Wright, C (2004)
BACKGROUND: Little is known about what characteristics of teams, staff and patients are associated with a favourable outcome of severe mental illness managed by assertive outreach. AIMS: To identify predictors of voluntary and compulsory admissions in routine assertive outreach services in the UK. METHOD: Nine features of team organisation and policy, five variables assessing staff satisfaction and burn-out and eleven patient characteristics taken from the baseline data of the Pan-London Assertive Outreach Study were tested as predictors of voluntary and compulsory admissions within a 9-month follow-up period. RESULTS: Weekend working, staff burn-out and lack of contact of the patient with out and lack of contact of the patient with other services were associated independently with a higher probability of both voluntary and compulsory admission. In addition, admissions in the past predicted further voluntary and compulsory admissions, and teams not working extended hours predicted compulsory admissions in the follow-up period. CONCLUSIONS: Characteristics of team working practice, staff burn-out and patients' history are associated independently with outcome. Patient contact with other services is a positive prognostic factor.